Implementasi Kegiatan Mengajar Melalui Program Surabaya Mengajar Untuk Mengasah Mahasiswa Dalam Keterampilan Berfikir Dan Bekerja Sama Pada Bidang Pendidikan - Cindy Rahmawati (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Abstract. Real Work Lecture (KKN) is one of the activities that must be carried out by all students of the University of 17 August 1945 Surabaya to apply the knowledge they have acquired while sitting on the lecture bench as well as a concrete form of community service. Devotion to society the author does with the